MANAGEMENT OF EMERGENCY NURSING CARE WITH SERVICE EXCELLENCE IN MR. D WITH SECOND-DEGREE BURNS AT THE EMERGENCY DEPARTMENT OF H. ADAM MALIK CENTRAL GENERAL HOSPITAL MEDAN NORTH SUMATRA PROVINCE IN 2025 - Noferia Gulo; Herna Rinayani Manurung; Lisbet Gurning; Fitri Maya Sinaga; Sanni Sihombing; Jane Evania Damanik; Dameria Sianipar (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
ABSTRACT Burns are a type of severe burn that not only affects the skin, but can also damage deeper tissue and cause systemic disorders in a person’s body. The goal is to maintain the safety of the victim, protect those who help, prevent infection, relieve pain and anxiety in a person, and maintain the victim’s condition until medical personnel arrive to provide further treatment. The method used in my research is a descriptive method, which systematically describes the nursing process carried out starting from assessing the patient’s condition, determining the diagnosis, formulating interventions, implementing actions, and evaluating the results of the implementation, as evidenced by documentation and using the Orem theory approach related to the problem of burns. According to WHO data in 2023, burns are a health problem that has recorded more than 265,000 people worldwide who have died. According to the Ministry of Health of the Republic of Indonesia (2020), the prevalence of burns in Indonesia in 2020 was recorded at 0.7%, a decrease of 1.5% compared to 2008 which reached 2.2%. According to Riskesdas, the number of burn patients in North Sumatra reached 1.0% of the total 5,401 people. Meanwhile, in Medan City, there were 89 people suffering from burns. Based on information obtained from the Medical Record book of the H. Adam Malik Medan General Hospital (RSUP), in 2021 there were 21 more patients, namely in 2022, becoming 43 people. continuing in 2023, increasing to 60 people. However, in 2024, there was a slight decrease, namely 52 patients were recorded, and burn data at the H. Adam Malik Medan Hospital on April 26-29, 2025 in the Surgical ICU Room there were 2 people. The selection of burn cases is the focus of discussion based on the contribution of nurses in holistic burn treatment, both in terms of physical, psychological, and educational, in order to accelerate the healing process related to SGDs No. 3 and 17. So, it makes me interested in taking the title of the final report with the title "Emergency Nursing Care Management with Grade II Burns on Mr. D. in the IGD Room of H. Adam Malik General Hospital, Medan, North Sumatra Province in 2025".